Comparison Between Two Definitions of Contrast-Associated Acute Kidney Injury in Patients With Congestive Heart Failure - Wang, Bo; Zheng, Yiying; Li, Huanqiang; Chen, Shuling; Zhou, Ziyou; Lun, Zhubin; Ying, Ming; Zhang, Lingyu; Mai, Ziling; Liu, Liwei; Zhou, Ziqing; Lin, Mengfei; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Different definitions of contrast associated acute kidney injury (CA-AKI) have predictive effects on prognosis. However, few studies explored the relation between these definitions and long-term prognosis in patients with congestive heart failure (CHF). Thus, we aimed to evaluate this association and compared the population attributable risks (PAR) of different CA-AKI definitions. Methods This study enrolled 2207 consecutive CHF patients undergoing coronary angiography (CAG) in Guangdong Provincial People’s Hospital. Two different definitions of CA-AKI were used: CA-AKIA was defined as an increase ≥ 0.5 mg/dl or > 25% in serum creatinine (SCr) from baseline within 72 h after CAG, and CA-AKIB was defined as an increase ≥ 0.3 mg/dl or > 50% in SCr from baseline within 48 h after CAG. Kaplan-Meier methods and Cox regression were applied to evaluate the association between CA-AKI with long-term mortality. Population attributable risk (PAR) of different definitions for long-term prognosis was also calculated. Results During the 3.8-year median follow-up (interquartile range 2.1-6.0), the overall long-term mortality was 24.9%, and the long-term mortality in patients with definition of CA-AKIA and CA-AKIB were 30.4% and 34.3%, respectively. We found that CA-AKIA (HR: 1.44, 95% CI 1.19-1.74) and CA-AKIB (HR: 1.48, 95% CI 1.21-1.80) were associated with long-term mortality. The PAR was higher for CA-AKIA (9.6% vs. 8.0%). Conclusions Our findings suggested that CA-AKI was associated with long-term mortality in patients with CHF irrespective of its definitions. For patients with CHF undergoing CAG, cardiologists should pay more attention to the presence of CA-AKI, especially CA-AKIA.